Biosorption of green and black tea polyphenols into Saccharomyces cerevisiae improves their bioaccessibility. (August 2015) - Jilani, Hanène; Cilla, Antonio; Barberá, Reyes; Hamdi, Moktar
Highlights: BT polyphenols have higher binding affinity to yeast cells than GT. Saccharomyces cerevisiae is a promising delivery system of tea antioxidants to the gut. Digested GT/BT samples showed higher antioxidant capacity after biosorption. After biosorption, non-gallated catechins were more stable to digestion than gallated catechins. Abstract: Infusions of green tea (GT) and black tea (BT) and the use of Saccharomyces cerevisiae as a natural matrix were employed to check the impact of biosorption on the possible fate of tea polyphenols in the gastrointestinal tract in terms of bioaccessibility and total antioxidant capacity (TEAC and ORAC assays). The maximum biosorption yields obtained were 47.61 ± 11.57 and 99.68 ± 5.25 mg/g from GT and BT infusions, respectively. A significant increase (p < 0.05) in the recovery of phenolic compounds was shown after in vitro digestion. The bioaccessible fractions generally exhibited higher antioxidant capacities in both tea infusions and suspensions of S. cerevisiae versus non-digested samples, with better values found after biosorption. The enhancement of the stability of two non-gallated catechins epigallocatechin (EGC) and epicatechin (EC) in tea infusion digests was verified after biosorption using TripleTOF-LC–MS–MS methodology. S . cerevisiae has been proven to be a promising delivery system for tea antioxidants and an effective means to protect their bioactivity during digestion.